The Gale encyclopedia of cancer a guide to cancer and its treatments - Longe, Jacqueline L.; Gale Group (Detroit, Michigan Thomson Gale, 2006)
Comprehensive survey of 120 cancers, cancer drugs, traditional and alternative treatments, side effects and diagnostic procedures.
v.1. A-K -- v.2. L-Z, general index.
Electronic reproduction.
Keywords: Cancer -- Encyclopedias; Oncology -- Encyclopedias; Electronic books